Human Rights Discourse, Gender and HIV and AIDS in Southern Malawi - Hayes, Nicole (Anthropologica, 2013)
This article explores how the proliferation of poorly translated human rights discourse has increased the vulnerabil ity of Malawian women and girls to HIV. In southern Malawi, "traditional" gender roles taught during initiations lay the foundation for women’s sexual submission to men, while en couraging men to think that they are entitled to sexual gratifi cation. In the wake of the recent democratic transition, young men have begun using imperfectly translated human rights rhetoric to rationalize formerly tabooed sexual behaviour and reinforce initiation gender norms. Women, meanwhile, are pre vented from exercising their own rights because it is their responsibility to preserve "culture."